Reactor scale-up of copper-chlorine cycle of hydrogen production from proof-of-principle to large engineering scale - Minato, Ray (Knovel, 2012)
Hydrogen produced from water splitting and clean energy sources is predicted by many to be a clean fuel that will serve as a substitute for conventional fuels because its oxidation does not emit greenhouse gases. Numerous thermochemical water splitting cycles have been proposed for clean hydrogen production. The copper-chlorine (Cu-Cl) cycle has a relatively low temperature requirement compared with other cycles and therefore is viewed as a promising method.
Keywords: Hydrogen as fuel.; Clean energy industries.; elektronické knihy; electronic books